العوامل المؤثرة في التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة: دراسة حالة لمواقف أساتذة التعليم المتخصص بمتوسطات والية تقرت - لبسيس خديجة (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة الى التعرف على العوامل المؤثرة في التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة، حيث ثم الانطلاق من تساؤل رئيسي مفاده: ما هي العوامل التي تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة من وجهة نظر أساتذة التعليم المتخصص؟ وتندرج ضمنها أسئلة فرعية نذكرها على النحو التالي: 1. هل العوامل المدرسية تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة؟ 2. هل العوامل المرتبطة بالأسرة تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة؟ 3. هل العوامل المتعلقة بالحالة الصحية تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة؟ ومنه طرحنا الفرضيات التالية. * تعتبر العوامل المدرسية عاملا يؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة. * تعتبر العوامل الأسرية عاملا يؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة. * تعتبر العوامل المتعلقة بالحالة الصحية عاملا يؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة. ولقد تم تطبيق المنهج الوصفي، وتم الاعتماد على الاستمارة كأداة منهجية بحثية خلال إجراء الدراسة الميدانية وفق منهج المسح الشامل وذلك نظرا لطبيعة الموضوع وحجم المجتمع الاحصائي كاملا الذي يتمثل في جميع أساتذة التعليم المتخصص العاملين على مستوى متوسطات ولاية توقرت والذي عددهم 30أستاذة تدرس الأقسام الخاصة، وهو العدد الإجمالي. ولقد تم التوصل الى جملة من النتائج أهمها: * العوامل المدرسية تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة من وجهة نظر أساتذة التعليم المتخصص. * العوامل المرتبطة بالأسرة تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة من وجهة نظر أساتذة التعليم المتخصص. * العوامل المتعلقة بالحالة الصحة تؤثر على التحصيل الدراسي لدى تلاميذ الأقسام الخاصة المدمجة. ""Résumé : فرنسية أو انجلزية This study aims to identify the factors influencing academic achievement among students in integrated special education classes. It is based on a central research question: What are the factors that affect academic achievement among students in integrated special education classes from the perspective of specialized education teachers? The study also explores the following sub-questions: 1. Do school-related factors influence the academic achievement of students in integrated special education classes? 2. Do family-related factors influence the academic achievement of these students? 3. Do health-related factors impact their academic performance? From these questions, the following hypotheses were formulated: School-related factors are considered to influence the academic achievement of students in integrated special education classes. Family-related factors are believed to have an effect on the academic achievement of these students. Health-related factors are also considered to impact their academic achievement. The descriptive method was adopted for this research, with the questionnaire serving as the primary data collection tool. A comprehensive survey approach was used due to the nature of the topic and the relatively small population size, which consisted of all 30 specialized education teachers working in integrated classes at the middle school level in the Wilaya of Touggourt. The study yielded several key findings, notably: School-related factors influence the academic achievement of students in integrated special education classes, according to the perspectives of specialized education teachers. Family-related factors impact academic achievement, as viewed by these educators. Health-related factors also play a significant role in influencing the academic performance of students in integrated special education settings. "
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع التربية.
Keywords: أستاذ تعليم متخصص; الأقسام الخاصة; الدمج; التحصيل الدراسي; Academic achievement; inclusion; special education classes; specialized education teacher.